Secondary resources of tomato processing as a valuable raw material for obtaining food ingredients - E. V. Lisovaya; E. P. Victorova; A. V. Sverdlichenko; N. N. Kornen (Новые технологии)
It is known that enterprises processing vegetables and fruits generate secondary resources (waste), in particular, pomace, in significant volumes. The most valuable, in terms of the composition and content of biologically active macro- and micronutrients, is tomato pomace. Tomato pomace is a valuable source of natural carotenoids, including lycopene, which exhibits high antioxidant activity. The article provides an overview of scientific research aimed at developing methods for extracting carotenoids, including lycopene, from recycled tomato processing resources. It has been shown that, in general, when extracting carotenoids, including lycopene, from secondary resources of tomato processing, various methods of drying and grinding the raw material are used, and then biologically active substances are extracted. It should be noted that the method of pretreatment of the feedstock, the nature of the solvent, the temperature and duration of the extraction process have a significant effect on the antioxidant activity and bioavailability of carotenoids obtained as a result of extraction. It is shown that the use of a pulsed electric field, treatment with enzymes and ultrasonic treatment of tomato pomace allow to intensify the process of extraction of carotenoids and maximally preserve their antioxidant properties. Thus, it can be concluded that tomato pomace is a valuable raw material for obtaining extracts of carotenoids and, first of all, lycopene, and the development of effec- tive modes of the extraction process that ensure the maximum manifestation of antioxidant properties and the bioavailability of the extracted substance is an urgent task.